Non-adhesive Contacts With Different Surface Tension Inside and Outside the Contact Area - Li, Qiang; Popov, Valentin L. (Frontiers in Mechanical Engineering, 2020)
In the last decade, the influence of surface tension on contact properties has attracted much atten-tion, especially in the context of contact of very soft materials (like gels) or contacts at the na-noscale. However, in the most current studies it is assumed that the tension of the surface inside and outside the contact area is the same. This practically means that the considered object is an elastic body "coated" with a tensed membrane. In real contacts, there is no reasons why the sur-face tension of the "free interface" and the "contact interface" should be equal. On the contrary, especially in contacts of soft bodies with hard solid indenters one can await that they are com-pletely different. In the present paper, we consider an elastic contact with account of different surface tension inside and outside the contact area. However, the considered contacts are still "non-adhesive". This means that the three surface energies in play (two surface energies of both bodies outside the contact and the interface energy in the contact region) fulfil the criterion that the work of separation vanishes. A numerical model based on the FFT assisted BEM is implemented and is illustrated with a few examples.